Vivências e trajetórias das mulheres no Mestrado Profissional em Matemática da UFPA - SANTOS, Celine Gabrielle Araújo dos (2022)
This research is linked to the research line “Mathematics Education”. It aimed to investigate the experiences and trajectories of women in postgraduate studies, especially in the professional at the Federal University of Pará Master's in Mathematics, on the campuses of Belem, Bragança and Castanhal, and their prospects for continuing studies in the area. Demystifying the idea that mathematics is not a strictly masculine science, in addition to historical support from women not as cited as men mathematicians. We present mathematical mathematics presents from antiquity to the contemporary world on different continents. The methodology used was qualitative research, carried out by an open presence for data collection observed via the environment for women that point to important results regarding the continuity of mathematics in the academy, regarding the continuity of mathematics in double and triple working hours. Even with difficulties, the master's students intend to continue their doctorate.